Minimal differences observed when comparing the morphological profiling of microglia obtained by confocal laser scanning and optical sectioning microscopy - Sânziana Godeanu; Sânziana Godeanu; Mădălina Iuliana Mușat; Anja Scheller; Anja Scheller; Eugen Osiac; Bogdan Cătălin; Bogdan Cătălin (Frontiers in Neuroanatomy)
BackgroundWhile widefield microscopy has long been constrained by out-of-focus scattering, advancements have generated a solution in the form of confocal laser scanning microscopy (cLSM) and optical sectioning microscopy using structured illumination (OSM). In this study, we aim to investigate, using microglia branching, if cLSM and OSM can produce images with comparable morphological characteristics.ResultsBy imaging the somatosensory microglia from a tissue slice of a 3-week-old mouse and establishing morphological parameters that characterizes the microglial branching pattern, we were able to show that there is no difference in total length of the branch tree, number of branches, mean branch length and number of primary to terminal branches. We did find that area-based parameters such as mean occupied area and mean surveillance area were bigger in cLSM isolated microglia compared to OSM ones. Additionally, by investigating the difference in acquisition time between techniques and personal costs we were able to establish that the amortization could be made in 6.11 ± 2.93 years in the case of countries with a Human Development Index (HDI) = 7–9 and 7.06 ± 3.13 years, respectably, for countries with HDI < 7. As such, OSM systems seem a valid option if one just wants basic histological evaluation, and cLSM should be considered for groups that demand higher resolution or volumetric images.